THE INTERSECTION OF TRIBAL ARTS AND ECOTOURISM: A CATALYST FOR SUSTAINABLE DEVELOPMENT IN KERALA, INDIA. - P. K, Manoj; Aithal, P. S. (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This paper seeks to explore the strategic role played by indigenous art forms in supporting the ecotourism value proposition in respect of the State of Kerala in India. It focuses on zones with high-biodiversity like Vazhachal, Wayanad, Idukki, Parambikulam etc. Using mixed-methods approach it analyses how tribal dance, rituals, handicrafts, etc. play a key role in sustainable regional economic development. Though the expansion of ecotourism could offer significant socio-economic benefits, which include a 32 percent rise in seasonal household earning for the respective artisans who participate in such activities, it could also pose ‘staged authenticity’ of cultural commodification. The study thus introduces a framework viz. Cultural Sustainability Index (CSI) and accordingly suggests a decentralized, ICT-integrated ‘Direct-to-Consumer’ model for the mitigation of economic leakage and preservation of the sanctity of tribal heritage.